Analgesic Effect of Low Energy Extracorporeal Shockwave Therapy on Chronic Plantar Fasciitis: A Randomized, Placebo-Controlled, Clinical Trial - Aftabi, Amirreza; Sarrafzadeh, Javad; Mohsenifar, Holakoo; Moghaddam, Navid (Journal of Clinical Physiotherapy Research, 2017)
Introduction: Plantar fasciitis is the most prevalent cause of pain in heels and widely treated using the shockwave therapy. Materials and Methods: Thirty patients (12 males and 18 females) randomly participated in this single blind clinical trial study that aimed to evaluate the effects of low energy extracorporeal shockwave therapy on pain in patients with chronic plantar fasciitis. Group 1 patients were treated with low energy shockwave and stretch, and group 2 control patients were treated by stretch and a placebo shockwave. The groups were demographically similar with respect to age, gender, and BMI. The patients were assessed for pain using the visual analog scale (VAS). Results: After 2 weeks of treatment, a significant difference in pain was observed between the two groups. The VAS results showed 76% reduction of pain in group 1 and 46% in group 2. Discussion: The use of low energy radial shockwave has significant short-term effects on pain relief in chronic plantar fasciitis and is, thus, recommended as a relatively painless and safe therapy prior to surgery. Keywords: Extracorporal Shockwave, Low Energy, Plantar Fasciitis